On Perfect 2‐Colorings of Johnson Graphs J(v, 3). Issue 6 (30th July 2012) - Gavrilyuk, Alexander L.; Goryainov, Sergey V.
Abstract We study the perfect 2‐colorings (also known as the equitable partitions into two parts or the completely regular codes with covering radius 1) of the Johnson graphs <inline-graphic mimetype="image" xlink:href="ark:/27927/pgg1x5tz9wx" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />J(v, 3). In particular, we classify all the realizable quotient matrices of perfect 2‐colorings for odd v. © 2012 Wiley Periodicals, Inc. J. Combin. Designs 21: 232–252, 2013